2021
DOI: 10.1126/scisignal.abe6156
|View full text |Cite
|
Sign up to set email alerts
|

TSHZ2 is an EGF-regulated tumor suppressor that binds to the cytokinesis regulator PRC1 and inhibits metastasis

Abstract: Unlike early transcriptional responses to mitogens, later events are less well-characterized. Here, we identified delayed down-regulated genes (DDGs) in mammary cells after prolonged treatment with epidermal growth factor (EGF). The expression of these DDGs was low in mammary tumors and correlated with prognosis. The proteins encoded by several DDGs directly bind to and inactivate oncoproteins and might therefore act as tumor suppressors. The transcription factor teashirt zinc finger homeobox 2 (TSHZ2) is enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…The first, TSHZ2, was responsible for the expression of ephrin RTK EPHA4 and its ligand EFNA5 ( 144 ), among others. Overexpressing TSHZ2 in mammary glands in mice accelerated their development while preventing malignancy ( 145 ), suggesting that this factor may help to regulate the ongoing growth of the distal tip. The other transcription predicted transcription factor was EHF, an epithelial-specific Ets-family transcription factor.…”
Section: Resultsmentioning
confidence: 99%
“…The first, TSHZ2, was responsible for the expression of ephrin RTK EPHA4 and its ligand EFNA5 ( 144 ), among others. Overexpressing TSHZ2 in mammary glands in mice accelerated their development while preventing malignancy ( 145 ), suggesting that this factor may help to regulate the ongoing growth of the distal tip. The other transcription predicted transcription factor was EHF, an epithelial-specific Ets-family transcription factor.…”
Section: Resultsmentioning
confidence: 99%
“…Other investigators have also reported that the overexpression of MerTK promotes cancer cell migration [39,48]. Interestingly, Uribe and colleagues reported that Axl, but not MerTK or Tyro3, correlated with the migration and invasion of colorectal cells [49]. Further, Tyro3 was identified as a direct tumor suppressor miRNA gene target that regulates the proliferation, migration, and invasion of human hepatocarcinoma cell lines [50].…”
Section: Discussionmentioning
confidence: 97%
“…Brynychova et al[38] studied the gene expression pro le of BC patients and found poor DFS in the PRC1 overexpression group, yet could not explain paclitaxel-induced PRC1 expression (Paclitaxel toxicity) by functional analyses. Uribe et al [39] successfully inhibits mammary tumors metastasis in mice by using TSHZ2, which binds to the cytokinesis regulator PRC1. A recent study has revealed the potential role of phosphorylating PRC1 in the progression of triple-negative breast cancer [40], Whether PRC1 plays a role as an indirect marker of BC metastasis still needs further validation.…”
Section: Discussionmentioning
confidence: 99%